Using Genetic Algorithm to Estimate Hydraulic Parameters of Unconfined Aquifers - Asghar Asghari Moghaddam; Vahid Nourani; Mehdi Kord (آب و فاضلاب, 2009)
Nowadays, optimization techniques such as Genetic Algorithms (GA) have attracted wide attention among scientists for solving complicated engineering problems. In this article, pumping test data are used to assess the efficiency of GA in estimating unconfined aquifer parameters and a sensitivity analysis is carried out to propose an optimal arrangement of GA. For this purpose, hydraulic parameters of three sets of pumping test data are calculated by GA and they are compared with the results of graphical methods. The results indicate that the GA technique is an efficient, reliable, and powerful method for estimating the hydraulic parameters of unconfined aquifer and, further, that in cases of deficiency in pumping test data, it has a better performance than graphical methods.